2016
DOI: 10.1096/fj.201601030r
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Bmal1 deletion increases monocyte recruitment and worsens atherosclerosis

Abstract: BMAL1, the nonredundant transcription factor in the core molecular clock, has been implicated in cardiometabolic diseases in mice and humans. BMAL1 controls the cyclic trafficking of Ly6c monocytes to sites of acute inflammation. Myeloid deficiency of also worsens chronic inflammation in diet-induced obesity. We studied whether myeloid deletion promotes atherosclerosis by enhancing monocyte recruitment to atherosclerotic lesions. By generating ;LysM mice on the Apoe background, we showed that deletion in myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 41 publications
1
50
0
1
Order By: Relevance
“…In mice, disrupted rhythms or clock gene deletion are associated with exacerbation of many disease states, including diabetes [27], cardiovascular disease[28, 29], inflammation [30, 31], and neurodegeneration [32]. In humans, circadian rhythm disturbances, often caused by employment and lifestyle issues such as night shift work, are associated with increased risk of diseases such as diabetes, breast cancer, and coronary artery disease [3336].…”
Section: The Mammalian Circadian Clockmentioning
confidence: 99%
“…In mice, disrupted rhythms or clock gene deletion are associated with exacerbation of many disease states, including diabetes [27], cardiovascular disease[28, 29], inflammation [30, 31], and neurodegeneration [32]. In humans, circadian rhythm disturbances, often caused by employment and lifestyle issues such as night shift work, are associated with increased risk of diseases such as diabetes, breast cancer, and coronary artery disease [3336].…”
Section: The Mammalian Circadian Clockmentioning
confidence: 99%
“…Previous studies in mice have shown that genetic disruption of the circadian molecular timekeeping mechanism causes cardiovascular pathology [15][16][17][18][19] . Mice lacking functional Bmal1, and Clock ∆19 mutants, both of which have impaired or arrhythmic circadian clocks, had increased pathological vascular remodeling compared to mice with functional clocks 17 .…”
mentioning
confidence: 99%
“…In the same line, Rev-erbα diminishes atherogenic lipoproteins plasma levels (82), modulates the inflammatory profile of macrophages toward an anti-inflammatory phenotype (83) while its activation reduced atherogenesis (84). Accordingly, BMAL1 regulates macrophage polarization as well as the cyclic trafficking of Ly6C hi monocytes and myeloid Bmal1 deletion increased monocyte recruitment and worsened atherosclerosis (Figures 2, 3) (85). Pro-inflammatory recruitment through the CCL2 (MCP-1)-CCR2 axis plays an important role in plaque development (86).…”
Section: Clock Control Of Nlrp3 Inflammasome Activation Il-1β Producmentioning
confidence: 92%